Various Adsorbents for Removal of Rhodamine B Dye: A Review - Zainab Mohammad Saigl (Universitas Gadjah Mada, 2021)
Lately, there has been an increase in dye manufacturing, resulting in increased environmental pollution. Recent studies show a wide availability of usage adsorbents, including banana peels, potatoes, algae, etc. Food and Drug Administration prohibited the use of Rhodamine B (RhB) for its toxicity and harmful effects. Therefore, this study presents a wide range of non-conventional low-cost alternative adsorbents to remove RhB dye from wastewater. It has been observed that the mechanism of the dye adsorption is focused on kinetics, isotherm, and thermodynamics models, which depend on the chemical nature of the materials and various physicochemical experimental conditions such as solution pH, initial dye concentration, adsorbent dosage, and temperature of the system. The kinetic data of adsorption of RhB dye usually follow the pseudo-first-order and pseudo-second-order kinetic models. Several studies revealed that Langmuir and Freundlich adsorption isotherm models are frequently used to evaluate the adsorption capacity of the adsorbents. Furthermore, thermodynamic examination showed that RhB adsorption was endothermic and unconstrained in nature. Thus, both photocatalytic degradation and adsorption methods offer good potential to remove RhB dye from industrial effluents. The work is in progress to evaluate the possibility of using other modified waste biomass for industrial pollution control.